PERANCANGAN MOULD PRODUK TUTUP GALON DISPENSER ANTI TUMPAH - Buyung Moslem; Yon Haryono; The, Jaya Suteja (CALYPTRA, 2018)
Anti-spilled dispenser galloncap product can’t be separate from human need for drinking water as a tool to help pouring water from gallon to dispenser without spilling the drinking water. The amount demand of those product is 25.000product per month with Rp 900,00 as the selling price. The purpose ofthis Final Project is to designing mould for anti-spilled dispenser gallon cap product within the specification of home industrial injection moulding machine. The result of mould designing is the mould consist of male, female, and stripper plate with the total dimension 200×105×150 mm.the mould have 2 cavity, a sprue and runnerswith total mass per injection 24,32 grams and the mould clamping force 8,9 tonnes. With those result is still under the capacity of the injection moulding machine. The mould having a cooling channel with the diameter is 10 mm and the length is 766 mm. The cooling channel is proved can handle to keep the mould in low temperature.Production cost for one product is Rp 303,00 so the product can be sell with lower price.